Preparation method of solid waste-based calcium-silicon-aluminum system cementing material

By adding modifiers, calcium carbide slurry, waste glass fiber and trimethylchlorosilane to the mixture of fly ash, steel slag and red mud, a solid waste-based calcium silicon aluminum system gelling material with high strength and crack resistance is prepared, which solves the problem of low utilization rate of solid waste resource utilization and unsatisfactory control of steel slag stability.

CN119822777AActive Publication Date: 2025-04-15WUHAN POLYTECHNIC UNIVERSITY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510068321.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize solid waste materials such as steel slag, fly ash and red mud, resulting in low resource utilization and unsatisfactory control effect of steel slag.

Method used

A method for preparing a solid waste-based calcium-silicon aluminum gelling material is proposed. By adding modifiers, calcium carbide slurry, waste glass fibers and industrial by-product trimethylchlorosilane to the mixture of fly ash, steel slag and red mud, a gelling material with high strength and crack resistance is obtained after stirring and curing.

Benefits of technology

The efficient resource utilization of a variety of solid waste has been achieved, and the prepared gelled materials have excellent compressive strength and crack resistance, and are suitable for building materials and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a solid waste-based calcium-silicon-aluminum system cementing material, which comprises the following steps: adding a modifier into fly ash, steel slag and red mud, then exciting by using carbide slag slurry to generate a synergistic effect, and adding an industrial byproduct trimethylchlorosilane to excite hydrolytic condensation of trimethylchlorosilane under an alkaline condition, thereby obtaining the solid waste-based calcium-silicon-aluminum system cementing material. Due to the formed polysiloxane, the added waste glass fibers are matched with a calcium silicate gel (C-S-H) system to form a more compact multi-dimensional structure, so that the strength of the calcium-silicon-aluminum system cementing material is further improved, and cracking is prevented; according to the preparation method, various solid wastes and industrial byproducts are used, the raw materials are easy to obtain, the method is simple, and the prepared material is excellent in performance after being cured and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid waste-based gel materials, and specifically relates to a method for preparing a solid waste-based calcium-silicon-aluminum system gelling material. Background Art

[0002] Steel slag, fly ash, and red mud are common solid waste materials. With the promotion of resource utilization, they are becoming more and more important. At present, there are many examples of solid waste utilization of steel slag, fly ash, and red mud, especially steel slag and fly ash, which have attracted much attention due to their huge reserves. For example, red mud is one of the three most difficult to utilize solid wastes. At present, a relatively systematic form of comprehensive utilization has been formed for red mud in terms of source reduction, resource recovery, soil remediation, etc., but the comprehensive utilization rate is only 7.6%, and further exploration and research on the resource utilization of red mud is still needed.

[0003] In terms of comprehensive utilization of metallurgy, steel slag is the most difficult to reuse among the three types of waste slag, because steel slag is mainly used in concrete and roadbed admixtures, and my country has no basic standards for products in this area. Compared with natural products, the quality is unstable, making it difficult to compete in the market. At present, the main technologies used by various companies to solve the stability of steel slag are hot stewing, hot pouring and other processes, but the effect of controlling its stability is not ideal. Steel slag grinding is a difficulty faced by all companies, which limits the comprehensive utilization of steel slag.

[0004] Red mud is highly alkaline and contains elements such as iron, silicon, and aluminum. Red mud is produced by the Bayer process and the sintering process. Red mud contains a lot of minerals and has a good effect on soil remediation. After mixing with water, red mud can adsorb heavy metal ions in it to improve water quality. It is a low-cost adsorbent. Red mud is harmless and environmentally friendly through dealkalization and desalination, but its applicability is not great. Red mud has relatively mature technologies for flue gas treatment and building materials, which can maximize the resource utilization of red mud and minimize the impact on environmental pollution. Fly ash is widely used, but mainly in the building materials industry, with a low level of utilization. Fly ash can be used to produce silicon-aluminum alloys and alumina, but cost and economic benefits are difficulties. As for the refinement of fly ash, high value-added comprehensive utilization should not be limited to the separation and extraction of high-content aluminum and silicon elements.

[0005] Scientific, reasonable and effective utilization of solid waste materials can not only bring good economic, environmental and social benefits, but a lot of research and development work is still needed to truly achieve comprehensive utilization.

[0006] Therefore, it is necessary to propose a method for preparing a solid waste-based calcium-silicon-aluminum system cementitious material to solve the problem of resource utilization of various solid wastes. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a method for preparing a solid waste-based calcium-silicon-aluminum system cementitious material to solve the problem of resource utilization of various solid wastes.

[0008] To solve the above problems, the scheme of the present invention is as follows: The first aspect of the present invention is to provide a method for preparing a solid waste-based calcium-silicon-aluminum system cementitious material, the steps comprising: S1. Adding a modifier and carbide slag slurry to a mixture of fly ash, steel slag and red mud for mixing and beating; S2. Add waste glass fiber and industrial by-product trimethylchlorosilane to the pulped material, and stir for 1-3 hours under sealed conditions to obtain a solid waste-based calcium-silicon-aluminum system gelling material; The mass percentages of fly ash, steel slag and red mud in the mixture are 60-80%, 5-20% and 10-30% respectively; the modifier includes desulfurized gypsum and silicate cement, and the total addition amount is 3-8wt%; the addition amount of carbide slag slurry is 50-80wt% of the mixture; The added amounts of the waste glass fiber and trimethylchlorosilane are 0.01-0.2% and 0.005-0.1% of the mass of the pulped material respectively.

[0009] Furthermore, in step S1, the mass ratio of silicate cement to desulfurized gypsum in the modifier is (1.5-5):1.

[0010] Furthermore, in step S1, the silicate cement is ordinary silicate cement.

[0011] Furthermore, in step S1, the ratio of the sum of the mass fractions of steel slag and fly ash in the mixture to the sum of the mass fractions of red mud and fly ash is (0.8-1):1.

[0012] Furthermore, in step S1, the water content of the carbide slag slurry is 40-60wt%.

[0013] Furthermore, in step S2, the length of the waste glass fiber is 0.5-2 mm, and it is cleaned before use. Furthermore, the red mud is obtained by sintering at 650-750°C; preferably, the sintering temperature is 700°C.

[0014] The second aspect of the present invention is to provide a solid waste-based calcium-silicon-aluminum system cementitious material, which is prepared and cured by the preparation method described in the first aspect.

[0015] Furthermore, the curing time is more than 28 days.

[0016] The third aspect of the present invention is to propose the application of the solid waste-based calcium-silicon-aluminum system cementitious material described in the second aspect in building materials.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the solid waste-based calcium-silicon-aluminum system cementitious material of the present invention comprises the following steps: adding a modifier to fly ash, steel slag and red mud, and then using carbide slag slurry to generate a synergistic effect after being excited; by adding trimethylchlorosilane, an industrial by-product, the trimethylchlorosilane can be excited to hydrolyze under alkaline conditions and release a large amount of heat before condensation; the formed polysiloxane enables the added waste glass fiber to form a tighter multi-dimensional structure with the calcium silicate gel (CSH) system, further improving the strength of the calcium-silicon-aluminum system cementitious material and preventing cracking; the preparation method uses a variety of solid wastes and industrial by-products, the raw materials are easily available, the method is simple, the prepared material has excellent performance after curing, and has broad application prospects. DETAILED DESCRIPTION The following examples are used to illustrate the present invention, but do not limit the scope of the present invention. Without departing from the spirit and essence of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0018] The reagents used in the following examples are commonly used reagents in the art, and are commercially available standard products unless otherwise specified. Unless otherwise specified, the experimental methods used are methods known in the art.

[0019] The steel slag used in the embodiment is purchased from Longze Water Purification Material Co., Ltd., Gongyi City, Zhengzhou, Henan Province, and the fly ash is derived from Longze Water Purification Material Co., Ltd., Gongyi City, Zhengzhou, Henan Province, and belongs to first-class fly ash, and red mud is purchased from Shandong Yizhu Material Co., Ltd. The water content of carbide slag slurry is 40-60wt%, and the calcium hydroxide content in the carbide slag slurry is 20-35wt%. Trimethylchlorosilane is a by-product formed by common industrial preparation of silane. Waste glass fiber is chopped glass fiber with a length of 0.5-2mm.

[0020] Example 1 A method for preparing a solid waste-based calcium-silicon-aluminum system gelling material, comprising the following steps: 1. The red mud is sintered at a temperature of 700°C and then crushed to obtain volcanic ash active red mud; 2. Add desulfurized gypsum and ordinary Portland cement PO•42.5 to the mixture of fly ash, steel slag and red mud sintered and crushed in step 1, respectively, and mix and stir. The mass percentages of fly ash, steel slag and red mud in the mixture are 60%, 20% and 20% respectively; the amount of desulfurized gypsum and Portland cement PO•42.5 added are 1wt% and 5wt% of the mixture respectively; then add carbide slag slurry in an amount of 60wt% of the mixture, and stir and beat at high speed after mixing; 3. Add 0.05% by weight of waste glass fiber and 0.05% by weight of trimethylchlorosilane to the pulped material obtained in step 2, and stir for 3 hours under sealed conditions to obtain a solid waste-based calcium-silicon-aluminum system gelling material; 4. Take an appropriate amount of material obtained in step 3 and pour it into a 40mm×40mm×160mm triple mold, shake it evenly, cover it with plastic wrap and let it stand, demould it after 1 day, and then put the sample into a standard curing box with (20±1)℃ and humidity ≥95% for curing until the specified age and then take samples for analysis.

[0021] Example 2 A method for preparing a solid waste-based calcium-silicon-aluminum system gelling material, comprising the following steps: 1. The red mud is sintered at 750°C and then crushed to obtain volcanic ash active red mud; 2. Add desulfurized gypsum and ordinary Portland cement PO•42.5 to the mixture of fly ash, steel slag and red mud sintered and crushed in step 1, respectively, and mix and stir. The mass percentages of fly ash, steel slag and red mud in the mixture are 70%, 15% and 15% respectively; the amount of desulfurized gypsum and Portland cement PO•42.5 added are 1wt% and 5wt% of the mixture respectively; then add carbide slag slurry in an amount of 70wt% of the mixture, and stir and beat at high speed after mixing; 3. Add 0.08% by weight of waste glass fiber and 0.03% by weight of trimethylchlorosilane to the pulped material obtained in step 2, and stir for 2 hours under sealed conditions to obtain a solid waste-based calcium-silicon-aluminum system gelling material; 4. Take an appropriate amount of material obtained in step 3 and pour it into a 40mm×40mm×160mm triple mold, shake it evenly, cover it with plastic wrap and let it stand, demould it after 1 day, and then put the sample into a standard curing box with (20±1)℃ and humidity ≥95% for curing until the specified age and then take samples for analysis.

[0022] Example 3 A method for preparing a solid waste-based calcium-silicon-aluminum system gelling material, comprising the following steps: 1. The red mud is sintered at a temperature of 700°C and then crushed to obtain volcanic ash active red mud; 2. Add desulfurized gypsum and ordinary Portland cement PO•42.5 to the mixture of fly ash, steel slag and red mud sintered and crushed in step 1, respectively, and mix and stir. The mass percentages of fly ash, steel slag and red mud in the mixture are 70%, 10% and 20% respectively; the amount of desulfurized gypsum and Portland cement PO•42.5 added are 1wt% and 5wt% of the mixture respectively; then add carbide slag slurry in an amount of 80wt% of the mixture, and stir and beat at high speed after mixing; 3. Add 0.03% by weight of waste glass fiber and 0.08% by weight of trimethylchlorosilane to the pulped material obtained in step 2, and stir for 2 hours under sealed conditions to obtain a solid waste-based calcium-silicon-aluminum system gelling material; 4. Take an appropriate amount of material obtained in step 3 and pour it into a 40mm×40mm×160mm triple mold, shake it evenly, cover it with plastic wrap and let it stand, demould it after 1 day, and then put the sample into a standard curing box with (20±1)℃ and humidity ≥95% for curing until the specified age and then take samples for analysis.

[0023] Comparative Example 1 The steps for preparing the solid waste-based calcium-silicon-aluminum system cementitious material are the same as those in Example 1, except that the red mud is not sintered.

[0024] Comparative Example 2 The steps for preparing solid waste-based calcium-silicon-aluminum system cementitious materials are the same as those in Example 1, except that the sintering temperature of the red mud in step 1 is 800°C.

[0025] Comparative Example 3 The steps for preparing solid waste-based calcium-silicon-aluminum system cementitious materials are the same as those in Example 1, except that in step 2, the carbide slag slurry is replaced by a sodium hydroxide solution of equal concentration.

[0026] Comparative Example 4 The steps for preparing solid waste-based calcium-silicon-aluminum system cementitious materials are the same as those in Example 1, except that in step 2, the added amounts of desulfurized gypsum and silicate cement PO•42.5 are 3wt% and 3wt% of the mixture respectively.

[0027] Comparative Example 5 The steps for preparing the solid waste-based calcium-silicon-aluminum system cementitious material are the same as those in Example 1, except that waste glass fiber is not added in step 3.

[0028] Comparative Example 6 The steps of the preparation method of the solid waste-based calcium-silicon-aluminum system cementitious material are the same as those of Example 1, except that no industrial by-product trimethylchlorosilane is added in step 3.

[0029] Test Case The compressive strength of cementitious materials is characterized by the compressive strength of slurry test blocks. When the test blocks are cured to the age, they are taken out of the curing box and the compressive strength test is performed on the test blocks. The compressive strength calculation formula is as follows: R S is the compressive strength of the test block, in MPa. F S is the maximum load that the test block can bear, in kN. AS is the force-bearing area of ​​the test block, in m 2 .

[0030] Test steps: Place the test block (40 mm×40 mm×160 mm) after standard curing in a compression and flexural testing machine and pressurize it at a loading speed of 2.4 kN / s until the test block is destroyed. Record the maximum loading pressure and use the formula to calculate the compressive strength of the sample.

[0031] Table 1: The initial and final setting times were measured according to GB / T1346-2001 “Test methods for water consumption, setting time and stability of cement of standard consistency”. The results are shown in Table 2.

[0032] Table 2: Comparison of initial setting and final setting time It is not difficult to see from Table 1 that the strength of the gel material after hydration in Examples 1-3 can reach 25Mpa in 28 days, while the use of unsintered red mud in Comparative Example 1 leads to a significant decrease in compressive strength. When the sintering temperature reaches 800°C in Comparative Example 2, the strength decreases slightly; the use of ordinary alkali solution for excitation in Comparative Example 3 also affects the compressive strength. The decrease in compressive strength in Comparative Example 4 shows that the addition ratio of desulfurized gypsum and silicate cement PO•42.5 also affects the compressive strength. Comparative Examples 5 and 6 do not use waste glass fiber and trimethylchlorosilane, respectively, which will lead to a significant decrease in compressive strength, indicating that glass fiber and trimethylchlorosilane play an important role in improving compressive strength.

[0033] In Table 2, the initial setting time of Examples 1-3 is maintained at about 50 minutes, and the final setting time is slightly greater than 100 minutes, which is significantly shorter than PO•42.5 cement, and has a significant advantage; at the same time, the setting time corresponding to Comparative Examples 1-4 is prolonged. The possible reason is that the red mud in Comparative Example 1 contains Al 2 O 3 Crystalline state, without sintering, leads to poor hydration reaction activity, while the sintering temperature in Comparative Example 2 is too high, which leads to the formation of Ca 2 Al 2 SiO 7 、NaAlSiO 4 The hydration reaction rate of the isocrystalline phase material is not as fast as that of the previous (amorphous phase) Al 2 O 3, thus showing reduced strength, and the crystalline state is less likely to hydrate. When comparative example 3 uses sodium hydroxide as a hydration activator, due to the lack of supplementary calcium, the hydration activity is relatively low and affects the compressive strength. Increasing the ratio of desulfurized gypsum to cement will lead to an excess of desulfurized gypsum, and other raw materials do not have the activity of cement, so the hydration reaction will slow down. The fact that comparative example 5 did not use waste glass fiber has little effect on the setting time, but the fact that comparative example 6 did not use trimethylchlorosilane resulted in a significantly longer setting time. The possible reason is that the addition of trimethylchlorosilane produces hydrolysis and polycondensation under alkaline conditions, thereby quickly increasing the viscosity of the system, and can combine with the calcium silicate gel (CSH) system and glass fiber to form a tighter multidimensional structure.

[0034] The above embodiments illustrate that the content of calcium, silicon, and aluminum oxides in red mud increases after sintering, and the hydration activity is enhanced. Similarly, there is a large amount of calcium hydroxide in the carbide slag slurry as solid waste, which supplements calcium while providing an alkaline environment, and further promotes the formation of gel products with silicon and aluminum active substances, mostly hydration products such as CSH, CASH, and calcium vanadate. Compared with steel slag, cement as an auxiliary additive improves the early strength and can provide more C2S and C3S to participate in the hydration reaction. Desulfurized gypsum mainly has a synergistic effect with cement to provide a gelled product, calcium vanadate, for the early hydration reaction. The preparation method provided by the present invention uses a variety of solid wastes, and the method is simple. The setting time of the prepared material is short, and the performance after curing is excellent, and it has a wide range of application prospects.

[0035] The present invention is not limited to what is described in the specification and implementation modes, and therefore, additional advantages and improvements can be easily realized by those familiar with the art. Therefore, without departing from the spirit and scope of the general concept defined by the claims and the equivalent scope, the present invention is not limited to specific details, representative schemes and described embodiments.

Claims

1. A method for preparing a solid waste-based calcium-silicon-aluminum system gelling material, characterized in that: Steps include: S1. Adding a modifier and carbide slag slurry to a mixture of fly ash, steel slag and red mud for mixing and beating; S2. Add waste glass fiber and industrial by-product trimethylchlorosilane to the pulped material, and stir for 1-3 hours under sealed conditions to obtain a solid waste-based calcium-silicon-aluminum system gelling material; The mass percentages of fly ash, steel slag and red mud in the mixture are 60-80%, 5-20% and 10-30% respectively; the modifier includes desulfurized gypsum and silicate cement, and the total addition amount is 3-8wt%; the addition amount of carbide slag slurry is 50-80wt% of the mixture; The added amounts of the waste glass fiber and trimethylchlorosilane are 0.01-0.2% and 0.005-0.1% of the mass of the pulped material respectively.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of silicate cement to desulfurized gypsum in the modifier is (1.5-5):

1.

3. The preparation method according to claim 1, characterized in that: In step S1, the ratio of the sum of the mass fractions of steel slag and fly ash in the mixture to the sum of the mass fractions of red mud and fly ash in the mixture is (0.8-1):

1.

4. The preparation method according to claim 1, characterized in that: In step S1, the water content of the carbide slag slurry is 40-60wt%.

5. The preparation method according to claim 1, characterized in that: In step S1, the red mud is sintered at 650-750°C.

6. The preparation method according to claim 6, characterized in that: The sintering temperature is 700°C.

7. The preparation method according to claim 1, characterized in that: In step S2, the waste glass fibers have a length of 0.5-2 mm and are cleaned before use.

8. Solid waste-based calcium-silicon-aluminum system cementitious material, characterized in that: The product is prepared and cured by the preparation method according to any one of claims 1 to 7.

9. The solid waste-based calcium-silicon-aluminum system cementitious material according to claim 8, characterized in that: The curing time is more than 28 days.

10. Use of the solid waste-based calcium-silicon-aluminum system cementitious material according to claim 8 or 9 in building materials.

Citation Information

Patent Citations

  • Cement-slag powder gel system with desulfurized gypsum as excitant

    CN101343161A

  • Cement-based filling material containing various solid wastes as well as preparation method and application of cement-based filling material

    CN112919874A

  • Fly ash and red mud geopolymer material and preparation method thereof

    CN113149525A

  • Premixed pump concrete prepared from fly ash and preparation method thereof

    CN114409361A

  • Alkali-activated cementing material for inhibiting saltpetering and preparation method thereof

    CN115403284A